1997
DOI: 10.1002/(sici)1097-4628(19970531)64:9<1749::aid-app11>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Polyethers containing coumarin dimer components in the main chain. I. Synthesis by photopolymerization of 7,7?-(polymethylenedioxy) dicoumarins

Abstract: Eight 7,7-(polymethylenedioxy)dicoumarins were successfully synthesized by solution condensation of 7-hydroxycoumarin (umbelliferone) or 7-hydroxy-4-methylcoumarin (4-methylumbelliferone) with various dibromoalkanes. Upon benzophenone-sensitized irradiation with 350 nm light in dichloromethane, the terminal coumarin chromophores dimerize to form polyethers containing coumarin dimer components in the main chain. The configurations of the coumarin dimer linkages were characterized by 1 H-NMR spectra. For unsubst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…1b), but the minimum does not reach zero as a few 4methylcoumarin groups may be photo-crosslinked in the last stage of photocleavage. 28 Fig. 1c shows that a short platform appears on the time dependence of the maximum absorbance at 320 nm due to the dynamic equilibrium between photo-crosslinking and photocleavage.…”
Section: Resultsmentioning
confidence: 98%
“…1b), but the minimum does not reach zero as a few 4methylcoumarin groups may be photo-crosslinked in the last stage of photocleavage. 28 Fig. 1c shows that a short platform appears on the time dependence of the maximum absorbance at 320 nm due to the dynamic equilibrium between photo-crosslinking and photocleavage.…”
Section: Resultsmentioning
confidence: 98%
“…Chen et al chemically synthesised polyesters, polyethers, and polyurethanes which contained pre-formed coumarin dimers in the main chain. [118][119][120] In these materials, coumarin dimer segments were exploited as sites for polymer photodegradation (by photo-chemical cleavage of the cyclobutanes) (Scheme 11). Chen demonstrated that exposure of the polyurethanes to 254 nm UV light caused photo-cleavage of the coumarin cyclobutanes and partial photo-degradation of the materials (Scheme 11).…”
Section: Linear Polymers Containing Pre-synthesised Cyclobutane Segme...mentioning
confidence: 99%
“…In Scheme , the reaction of coumarins 2 and 3 with methyl methacrylate under 365 nm UV irradiation resulted in the formation of both cyclobutane photodimers 4a and 4b in the 30–35% yield range together with [2 + 2]-cycloaddition products 5­(a,b) and 5′(a,b) also in the 30–35% combined yield range (Scheme , eq 1). Under our conditions, [2 + 2]-photocycloaddition of coumarins 2 and 3 afforded syn -head-to-tail ( syn -HT) isomers 4a and 4b as major products together with anti -head-to-head as minor isomers ( anti -HH, Scheme , eq 2), which could be obtained as major products if the reaction solvent was changed to acetone in the presence of benzophenone as a photosensitizer . To verify if the photoreactions involve radicals during the reaction courses, we used hydroquinone 7 as a radical quencher (Table S1).…”
Section: Resultsmentioning
confidence: 99%